Kinematic evolution of the Pieniny Klippen Belt in Cenozoic (Ukrainian Carpathians) - Murovskaya, A. V.; Nakapelyukh, M. V.; Vikhot, Yu. M.; Shlapinskiy, V. E.; Bubnyak, I. N.; Mychak, S. V. (Geofizicheskiy Zhurnal, 2016)
The data on surface, subsurface and deep structure of the Pieniny Klippen Belt (PKB) have been summarized and new results of its geological-structural and fault kinematic studies within the Ukrainian part of the Eastern Carpathians have been presented. In its contemporary appearance as a narrow strongly tectonized zone between the Outer Carpathians and Trans-Carpathian trough PKB was formed in Oligocene—Miocene in the place of ancient ocean. On the surface it is situated within the rootless Pieniny nappe and in the deep it is a steeply dipping deformation zone which developed under compression, simple dextral strike-slip, transtension and transpression. Mesostructures of horizontal shortening and vertical elongation, thrusts and thrust-related folds as well as structures of lateral extrusion — dextral strike-slip along sub-meridional slicken-sides correspond to SW—NE 220° trending compression and correlate with the stage of Alcapa microplate progression in NE direction in Oligocene—Early Miocene. In Early Miocene as a result of counter-clockwork rotation of Alcapa dextral strike-slip deformation is concentrated in boundary zone between Alcapa and accretionary prism of Ukrainian Flysch Carpathians. The stress fields of strike-slip type with orientation of compression axis SE 165—SW 215° and its “rotation” in a zone of simple shear correspond to this stage. Present deformation regime is characterized as transpressure with SW—NE orientation of compression axis.